Reflections on "Grounded theologies’ : ‘Religion’ and the ‘secular’ in human geography," by Justin Tse - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2024)
In this chapter, Justin Tse reflects on his motivations and impetuses in writing his paper “Grounded Theologies: ‘Religion’ and the ‘Secular’ in Human Geography,” originally published in 2014. The chapter also reflects on how the original paper has foreshadowed developments since.